REPRESENTASI KETIDAKADILAN GENDER TOKOH PEREMPUAN DALAM NOVEL RE: DAN PEREMPUAN KARYA MAMAN SUHERMAN - Birahmatika Zaidan Prassetio; Robert Rizki Yono; Ubaedillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the forms of gender injustice and the types of struggles of female characters in the novel Re: and Women by Maman Suherman. This research uses a liberal feminist approach with a qualitative descriptive method. Data is collected from quotations that represent injustice and women's struggles in the novel. The results of the study show that female characters experience gender injustice in various forms, such as marginalization, subordination, stereotypes, violence, and workload. This injustice arises from a patriarchal social structure that places women in a socially, economically, and psychologically weak position. However, the female characters in this novel also demonstrate various forms of resistance and struggle, particularly in the fields of education, economy, and freedom of expression. Through these struggles, they seek to liberate themselves from structural domination and demand their rights as.